Students’ Perception on the Use of ELSA Speak Application in Pronunciation - Mochamad Fazri; Puji Siswanto; Obay Jambari (English Education:Journal of English Teaching and Research, 2026)
This study aims to investigate Indonesian EFL learners’ perceptions of using the ELSA Speak application for pronunciation learning. This study employed a qualitative case study approach to investigate students’ perceptions of using the ELSA Speak application in pronunciation learning. The data of the study were collected through semi-structured interviews with second-semester English Education students at a university in Indonesia. The collected data were analyzed using thematic analysis. The findings of the study reveal that students perceive ELSA Speak as a highly beneficial tool for improving pronunciation skills. Students perceived ELSA Speak positively because it provides immediate corrective feedback, is easy to use, and supports pronunciation practice. However, ELSA Speak also presents several challenges, including internet connectivity issues and initial difficulty in navigating and understanding the application interface. These results align with the Technology Acceptance Model (TAM), emphasizing the app's perceived usefulness and ease of use. The research contributes to the discourse on technology-enhanced language learning by validating ELSA Speak's efficacy while identifying areas for improvement, such as accessibility and interactivity. In brief, Indonesian EFL learners perceived ELSA Speak as an alternative tool for teaching and learning pronunciation.